EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) DALAM MENINGKATKAN KETERAMPILAN KOLABORASI MURID KELAS IV SD - Oktaviana, Reginsa; Yunitasari, Indah; Setiawan, Angga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Teams Games Tournament (TGT) learning model on the collaboration skills of fourth grade students in IPAS learning. The background of this study was the low collaboration skills of students during the learning process, where students were still passive in group discussions. This research used a quantitative approach with a quasi-experimental design and Nonequivalent Control Group Design. The research was conducted at SDN 1 Ngulankulon and SDN 2 Ngulankulon in the 2025/2026 academic year. Data collection techniques included tests, observations, and documentation. Data were analyzed using normality tests, homogeneity tests, Independent Sample t-test, and N-Gain tests. The results showed that the TGT learning model had a significant effect on students’ collaboration skills with a significance value of 0.023 < 0.05. The average posttest score of the experimental class was higher than the control class, namely 93 and 89. The N-Gain results also indicated that the TGT model was sufficiently effective in improving students’ collaboration skills. Therefore, the Teams Games Tournament (TGT) learning model can be used as an alternative learning model to improve collaboration skills in elementary school students.